Consciência fonológica nos desvios fonológicos avaliação e terapia - Dias, Roberta Freitas (2015)
This thesis had the purpose of analyzing the impact of phonological properties of words which belong to two phonological awareness tasks, as in children with typical phonological development as in children with phonological disorders. Besides, two therapeutic approaches for phonological disorders were proposed, therapy based on stimulation of phonological awareness skills and phonological therapy associated with stimulation of phonological awareness skills, which were compared with a consecrated approach, the Modified Maximal Opposition Model (BAGETTI, MOTA, KESKE-SOARES, 2005). For this study, there were 80 children, 55 with typical phonological development and 25 with phonological disorders, all Brazilian Portuguese monolingual speakers. To analyze the impact of the phonological properties of the words which belong to the phonological awareness tasks, it was used an evaluation instrument, organized by the research author, which consists of syllable segmentation and segmental recognition tasks. As children with typical phonological development as children with phonological disorders responded the instrument. The analyzed phonological properties from the given responses were: word length, syllable structure and segmental properties (MA). These data were statistically analyzed through the Chi-Square Test (p<0.05). About the therapeutic approaches, they were applied in seven children with phonological disorders, divided in three groups: purely phonological therapy, therapy based on stimulation of phonological awareness skills and phonological therapy associated with stimulation of phonological awareness skills. It was analyzed the phonological system, the phonetic inventory, the percentage of correct consonants and the phonological awareness. These children received therapy for, at least, 25 sessions and their data were analyzed pre- and post-therapy, in a descriptive way. The results obtained through the applied evaluation instrument indicated that the phonological properties of the words which were part of both applied tasks had effect in the responses of the typical children and in the responses of the children with phonological disorders. The children with typical phonological development obtained more positive results, when compared with children with phonological disorders. The therapeutic approaches proposed by the research author, about the stimulation of phonological awareness skills, promoted the phonological systems reorganization and the increase of percentage of correct consonants in children who received therapy through the mentioned approaches. The results related to phonological awareness showed that the approaches regarding stimulation of phonological awareness skills benefited the development of these skills, when compared with the purely phonological therapy. Thus, it was observed that the stimulation of phonological awareness skills may promote the reorganization of the phonological system of children with phonological disorders, as well as provide these skills development in this population.